Leading-edge flow separation control over a NACA 0012 aerofoil with DBD plasma actuators - Song, Longfei (2018)
An experimental investigation has been conducted in a low-speed wind tunnel at the University of Nottingham to study the flow separation control capability of a wall-normal plasma jet by DBD plasma actuator over a NACA 0012 aerofoil. As an active flow separation control technique, DBD plasma actuators could be applied when required to manipulate a flow. They are surface-mounted and require no moving parts, ducts, holes or cavities, so no profile drag penalty will be caused. Moreover, they are fast responding since they are purely electrical devices and could be operated at a higher frequency relative to other flow control techniques. DBD plasma actuators are easy to manufacture, low in weight, low energy consuming and can be easily fitted to aerofoils. Therefore, they are ideal tools to control the flow separation around aerofoil. Up to date, wall plasma jet was used to add momentum to flow directly so that flow becomes more energetic and capable of withstanding adverse pressure gradient. In this study, a wall-normal plasma jet by steady actuation of plasma actuator was investigated and PIV results show that it has the capability of controlling the separation around aerofoil at post-stall angles of attack. The wall-normal jet is bent towards freestream direction and some small-scale vortical structures are created due to the interaction between the wall-normal plasma jet and freestream. These vortical structures could promote mixing and transport high-momentum fluids into the boundary layer, which affects the flow above the suction surface significantly. Moreover, unsteady actuation of plasma actuator was also utilised to control the flow separation around aerofoil. It was found that it has a stronger ability to control flow separation even at a much lower energy consumption than steady actuation of plasma actuator. PIV measurements demonstrate that separated flow could be reattached at post-stall angle of attack of 14° with only 10% of the energy consumption by steady actuation. Flow is well organized and a series of large-scale vortices are created with periodic activation of plasma actuator, these vortices enhance entrainment and the outwards transport of fluids from aerofoil surface leads to a favourable pressure gradient, resulting in a control of flow separation.